THE BURDEN OF NEUROLOGICAL DISEASE IN THE ACUTE INPATIENT HIV POPULATION; AN AUDIT OF 73 CONSECUTIVE ADMISSIONS. Issue 11 (9th October 2013) - Brown, Rachel; Nelson, Mark; Kennedy, Angus; Janssen, John; Davies, Nicholas WS
Abstract : Introduction: Neurological complications of HIV infection may result from opportunistic infection, tumour, direct effects of the virus, or drug toxicity. The changing demographics of HIV infection in the UK, particularly the ageing population, are likely to alter the spectrum of neurological disease seen in HIV centres. We audited acute inpatients with HIV infection to describe the current prevalence of neurological symptoms and signs in our cohort. Methods: Consecutive patients admitted to an acute HIV ward over a 3–month period underwent neurological assessment. Data collected included history of HIV infection, history of neurological disorders and presence of neurological symptoms. A screening neurological examination was performed on all patients. Data was analysed using Excel and GraphPad. Results: Of 84 patients admitted, 73 were assessed, 6 were excluded as too unwell to complete assessment and 5 patients were missed. Of the patients assessed, 63 patients were male. Median age was 44 years (range 25–70 years). Median nadir CD4 count was 100 cells/μL (range 0–604, n=61) and median CD4 count at assessment was 366 cells/μL (1–1396, n=72). There were 65 patients (89%) anti–retroviral–drug–treated with a median duration of treatment 4 years (range 5 days–26 years). There was a high incidence of pre–existing neurological disorders: 41% reported previously diagnosed neurological or ophthalmic disorders and 27% patients reported previous assessment by a neurologist. Neurological or ophthalmic symptoms were the reason for admission in 7 patients (10%) and 3 patients (4%) respectively, and were the 4th most common reason for presentation by organ system. Six of these patients had new CNS infections, including cerebral toxoplasmosis (1 patient), cryptococcal meningitis (1 patient), progressive multifocal leukoencephalopathy (1 patient), CMV retinitis (2 patients) and neurosyphilis (1 patient). One patient was diagnosed with cerebral toxoplasmosis later during a prolonged admission for a respiratory infection. CNS infection as cause for admission was significantly associated with current CD4 <100 cells/μL (p=0.009). The frequency of neurological symptoms was high (73% patients) while 60% patients had abnormal neurological signs on clinical examination. Clinical examination frequently revealed asymptomatic neurological signs, for example signs indicative of mild distal symmetrical sensory neuropathy. Inpatient referral to the neurology team was made for 8 (11%) patients. Conclusions: This audit demonstrates a high incidence of neurological symptoms and signs in the acute HIV setting. Physicians treating HIV–infected inpatients should be vigilant for neurological diseases. HIV centres require both neurological liaison services as well as access to neurological investigations. Service development and commissioning plans for HIV inpatient care need to incorporate access to neurological expertise.